ANALYSIS AND MONITORING THE NETWORK TRAFFIC IN THE PROCESS OF CONNECTING TO INDUSTRIAL SIEMENS CONTROLLERS: ANALYSIS AND MONITORING THE NETWORK TRAFFIC IN THE PROCESS OF CONNECTING TO INDUSTRIAL SIEMENS CONTROLLERS - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper analysis and monitoring of network traffic in the process of connecting to industrial Siemens controllers in the Faculty of Technical Sciences is made.